Synthesis and characterization of silver nanoparticles-doped titanium (IV) oxide thin films. Issue 1 (March 2020) - Balogun, SW; Abdulhamid, AB; Sanusi, YK; Adedokun, O
Abstract: Current advancements in nanotechnology appear to open a more efficient, stable, and cheaper way of producing solar cells to replace the too expensive means of inorganic solar cells production. The creation of nanoscale materials for advanced structures has led to a growing research interest in the area of photovoltaic energy conversion using photovoltaic devices. This research investigates the impact of annealing temperature on the optical properties of silver nanoparticles-doped titanium (IV) oxide thin film (TiO2 :AgNPs) deposited by spin-coating method on glass substrate. AgNPs were prepared using the leaf extract of Gliricidia sepium as a reducing agent for silver nitrate. Deposition of TiO2 :AgNPs composite solution was performed in different volume ratio. Deposition of TiO2 :AgNPs volume ratio (1: 0.2) was performed with different spin-coating speed for 30 seconds at 7 different thicknesses. Characterization of the optical properties of thin films was carried out by using a UV-vis single beam spectrophotometer; this was used to calculate the absorbance and the bandgap energy. Sixteen 16 samples of TiO2 :AgNPs deposited at 1000 rpm on the glass substrate were annealed at temperature range of 50 to 425 °C with step of 10 °C interval in a tubular furnace. It was observed from the results that the peak absorption of photon energy occurred at 375 °C in the visible spectrum of the wavelength band. The optimal thickness for peak absorbance of the TiO2 :AgNPs blend layer occurred at 115 nm in the visible spectrum and at the corresponding spin speed of 1000 rpm. The optimized fabrication process with blend layer thickness of 115 nm yielded the best absorbance at an annealed temperature of 375 °C in the visible spectrum. The volume ratio of (1:0.2) gave the peak absorption at 0.75 au. At 1000 rpm with the corresponding thickness of 115 nm, TiO2 :AgNPs blend has the peak absorbance. The energy band gap of the blend thin film is 3.58 eV at 375 °C in the visible spectrum of wavelength band. The result obtained showed that AgNPs enhanced light absorption, broadened absorption spectral range and thermal stability of titanium (IV) oxide film. The result can be used as a guideline in the design and fabrication of solar cells.